RAW REHMANNIA RADIX POLYSACCHARIDE CAN EFFECTIVELY RELEASE PEROXIDATIVE INJURY INDUCED BY DUCK HEPATITIS A VIRUS - Song, Meiyun; Chen, Yun; Du, Hongxu; Zhang, Shuaibing; Wang, Yixuan; Zeng, Ling; Jintong Shi, Jingjing Yang; Wu, Yi; Wang, Deyun; Hu, Yuanliang; Liu, Jiaguo (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Duck viral hepatitis (DVH), caused by duck hepatitis A virus (DHAV), is a fatal contagious infectiousdisease which spreads rapidly with high morbidity and high mortality, and there is no effective clinical drug againstDVH.Materials and Methods: Raw Rehmannia Radix Polysaccharide (RRRP), Lycii Fructus polysaccharides andAstragalus Radix polysaccharides were experimented in vitro and in vivo. Mortality rate, livers change, liver lesionscoring, peroxidative injury evaluation indexes in vitro and in vivo, and hepatic injury evaluation indexes of optimalone were detected and observed in this experiment.Results: RRRP could reduce mortality with the protection rate about 20.0% compared with that of the viral control(VC) group, finding that RRRP was the most effective against DHAV. The average liver scoring of the VC, blankcontrol (BC), RRRP groups were 3.5, 0, 2.1. Significant difference (P<0.05) appeared between any two groups,demonstrating that it can alleviate liver pathological change. RRRP could make the hepatic injury evaluation indexessimilar to BC group while the levels of the VC group were higher than other two groups in general. The levels of SOD,GSH-Px, CAT of RRRP group showed significant higher than that of VC group while the levels of NOS and MDAshowed the opposite tendency, thus, RRRP could release peroxidative injury.Conclusion: RRRP was the most effective against duck hepatitis A virus (DHAV). RRRP could reduce mortality,alleviate liver pathological change, down-regulate liver lesion score, release peroxidative injury and hepatic injury. Theantiviral and peroxidative injury releasing activity of RRRP for DHAV provided a platform to test novel drug strategiesfor hepatitis A virus in human beings.